Interdisciplinary education: a proposal. - Syed Alwi Shahab, (Universiti Kebangsaan Malaysia, 1974)
The products of our Universities are becoming less and less adequate to meet the demands imposed by an increasingly complex and rapidly changing environment. This is partly due to the current curricular arrangements and, more fundamentally, to the vertical, compartmentalised ordering of knowledge which is typical of our university syllabi. Even the so-called liberal education programmes are merely patchwork made up from disparate disciplines. A proposal is here made for an attempt to review and reconstruct our knowledge maps from an integrated multi and inter-disciplinary perspective. This opens up channels for new and refreshing curricular designs.